Carrier Frequency Offsets Problem in DCT-SC-FDMA System: Investigation and Compensation. (13th September 2010) - Al-kamali, Faisal S.; Dessouky, Moawad I.; Sallam, Bassiouny M.; Shawki, Farid; Abd El-Samie, Fathi E.
Abstract : The Single-Carrier Frequency Division Multiple Access (SC-FDMA) system is a well-known system, which has recently become a preferred choice for uplink channels. In this system, the Carrier Frequency Offsets (CFOs) disrupt the orthogonality between subcarriers and give rise to Intercarrier Interference (ICI), and Multiple Access Interference (MAI) among users. In this paper, the impact of the CFOs on the performance of the Discrete Cosine Transform (DCT) SC-FDMA (DCT-SC-FDMA) system is investigated. Then, a new low-complexity joint equalization and CFOs compensation scheme is proposed to cancel the interference in frequency domain. The Minimum Mean Square Error (MMSE) equalizer is utilized in the proposed scheme. A hybrid scheme comprising MMSE equalization, CFOs compensation, and Parallel Interference Cancellation (PIC) is also suggested and investigated for further enhancement of the performance of the DCT-SC-FDMA system with interleaved subcarriers assignment. For simplicity, this scheme will be referred to as the MMSE+PIC scheme. From the obtained simulation results, it is found that the proposed schemes are able to enhance the system performance, even in the presence of the estimation errors.